From Frontier to Border: The 1845 Health Code and the Structuring of Greece’s Quarantine System - Barlagiannis, Athanasios (The Historical Review/La Revue Historique, 2021)
How did health technologies influence border construction, identity formation and political developments in nineteenth-century Greece? The study focuses on the 1845 Health Code, which instituted a comprehensive system of coastal and inland lazarettos and health offices. It presents the development of the health border system prior to the enactment of the code and explains the timing of the enactment of that legislation. Compared to other important health legislation, the code had a long gestation as a result of the combined and often conflicting influences of five interrelated factors: commercial relations with the Ottoman Empire; the health preoccupations of Western European states; the significance of the plague; the cultural orientation of the Greek state towards “Western civilisation”; and the capacity of the Greek administration to exercise control over its territory. The code, a step towards the geographical and cultural reorientation of a former Ottoman province as a sovereign state, defines the slow passage from the empire’s frontiers to the state border system.